Parking System Mobile Application by Using Internet of Things (IoT) - Thillai Nadarajan, Vemal Raj (IRC, 2019)
The rapid growth in statistics era has created several possibilities round the sector as the usage of technology round us will increase each day. Therefore, there was a problem for the students, academics and also the traffic in locating the exact parking space across the campus. One of the primary problems of this non-systematic method of parking is illegal parking carried out via all the people who are having tough time locating a parking. Furthermore, it's also giving a tough time for other humans so that it will put off their cars or also to skip by means of the road. On account that returned then, Universiti Teknologi PETRONAS (UTP) has brought a parking allocation for both lecturers and college students primarily based on the benefit. This allocation changed into fairly encouraged with the aid of the lecturers because of the range of automobiles within the campus since lower back then. However, there had been nevertheless parking accomplished illegally by using the scholars for you to attend lessons on time and fail to find the appropriate parking spot.